Pleurotus pulmonarius (Fr.) quel crude aqueous extract ameliorates wistar-kyoto rat thoracic aortic tissues and vasodilation responses - Noor Fazila Mohd Yahaya; Norhaniza Aminudin; Noorlidah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pleurotus pulmonarius crude aqueous (CA) extract was previously reported to have therapeutic potential, thus its ability to alleviate serum total cholesterol, vasodilation, and improve the aortic tissue structure in hypercholesterolemia rat model was studied. Eight groups of Wistar-Kyoto rats were involved including normal (G1), hypercholesterolemia (G2), treatment (G3 to G5) and prevention (G6 to G8). Two doses of CA; 0.5 g/kg body weight (BW), 2.0 g/kg BW, and simvastatin 10 mg/kg BW were orally fed to the rats (G3 to G8). Treatment groups were induced with hypercholesterolemia and later treated with CA/simvastatin, while prevention groups were given both hypercholesterolemia-diet and CA/simvastatin simultaneously. The thoracic aortic rings (TAR) were subjected to contractility study and histopathology examination. In organ bath analysis, pre-contracted TAR of G1 with phenylephrine (PE) achieved 60% vasodilation response towards acetylcholine (ACh) whereas TAR of G2 unable to respond to ACh. G3 to G5 groups failed to dilate when induced with ACh whereas G6 to G8 groups showed a slight improvement. The repeated precontracted TAR of G1 and G2 significantly dilated with the presence of CA and simvastatin. TAR of G1 achieved 100% vasodilation at 3.0 mg/mL CA and 2.4 mg/mL simvastatin. TAR of G2 achieved 73% vasodilation at 6.0 mg/mL CA whereas 76.8% dilation recorded for simvastatin at 4.8 mg/mL. Histopathological examination found that CA was able to improve the structure of the aortic cells. These observations suggest that CA helps to improve tissue condition and vasodilation of the hypercholesterolemic aorta.